Genetic Link Determining the Maternal-Fetal Circulation of Vitamin D - Sampathkumar, Aparna; Tan, Karen M.; Chen, Li; Chong, Mary F. F.; Yap, Fabian; Godfrey, Keith M.; Chong, Yap Seng; Gluckman, Peter D.; Ramasamy, Adaikalavan; Karnani, Neerja (Frontiers in Genetics, 2021)
Vitamin D is an essential micronutrient whose demand is heightened during pregnancy to support the growth of the fetus. Furthermore, the fetus does not produce vitamin D and hence relies exclusively on the supply of maternal vitamin D through placenta. Vitamin D inadequacy is linked with pregnancy complications and adverse infant outcomes. Hence early predictive markers of vitamin D inadequacy such as genetic vulnerability are important to both mother and offspring. In this multi-ethnic Asian birth cohort study, we report the first genome-wide association analysis (GWAS) of maternal and fetal vitamin D in circulation. For this, 25-hydroxyvitamin D (25OHD) was measured in the antenatal blood of mothers during mid gestation (n=942), and the cord blood of their offspring at birth (n=812). ~7 million SNPs were regressed against 25OHD concentrations to identify genetic risk variants. 41% of mothers had inadequate 25OHD (≤75nmol/L) during pregnancy. Antenatal 25OHD was associated with ethnicity [Malay (Β=-22·32nmol/L, p=2·3x10-26); Indian (Β=-21·85, p=3·1x10-21); reference Chinese], age (Β=0·47/year, p=0·0058), and supplement intake (Β=16·47, p=2·4x10-13). Cord blood 25OHD highly correlated with antenatal vitamin D (r=0·75) and was associated with ethnicity [Malay (Β=-4·44, p=2·2x10-7); Indian (Β=-1·99, p=0·038); reference Chinese]. GWAS analysis identified rs4588, a missense variant in the GC gene encoding vitamin D binding protein (VDBP), and its defining haplotype, as a risk factor for low antenatal (Β=-8·56/T-allele, p=1·0x10-9) and cord blood vitamin D (Β=-3·22/T-allele, p=1·0x10-8) in all three ethnicities. We also discovered a novel association in a SNP downstream of CYP2J2 (rs10789082), a gene involved in 25-hydroxylation of vitamin D, with vitamin D in pregnant women (Β=-7·68/G-allele, p=1·5x10-8), but not their offspring. As the prevention and early detection of suboptimal vitamin D levels are of profound importance to both mother and offspring’s health, the genetic risk variants identified in this study allow risk assessment and precision in early intervention of vitamin D deficiency.